Os marcadores conversacionais no WhatsApp: análise da conversação virtual - Costa, Ana Cecília de Sousa (2021)
This dissertation has the general objective of analyzing the uses and functions of conversational markers, such as the beginning, maintenance and conclusion of the speech shifts, agreement and disagreement, present in messages from the WhatsApp application, in order to perceive the functions that these verbal, non-verbal and supra-segmental markers express in the virtual oralized writing of 8th grade students of a public school in Fortaleza. The theoretical and analytical bias of this work was based on Conversation Analysis and Network Conversation Analysis, referenced by the works of Marcuschi (2003) and Recuero (2014), respectively. As for the methodology, both the dialogues of the WhatsApp group in which the 8th grade students are interacting were used, as well as the result of the applied questionnaire (support corpus) with the same students, whose objective was to understand, from their own discourse, what are your intentions and communicative purposes when using some of the markers found in the main corpus. The results point out, as well as in the specific work assumptions, that students rely on conversational markers to constitute interaction. These markers, however, perform different functions, such as: guiding the progress and negotiation of the conversation; connect the communicative units; indicate the context; schedule shift changes, etc. In addition, the use of paralinguistic resources, such as non-verbal conversational markers, is recurrent to simulate gestures, movements, smiles, looks with the intention of maintaining and establishing closer contact with the interlocutor, similar to that of face to face. The markers identified in the dialogues still demonstrate that, in virtual media, the intentionality of resources is even more evident, especially when we look at it from the perspective of linguistic (im) politeness. In this sense, there is the provocation for new research to address the gaps present in the research because of time.